The determinants of housing price index in Malaysia / Mohd Hazwan Harman Shah - Harman Shah, Mohd Hazwan (Faculty of Business and Management, 2018)
This study is to research about the Determinants of Housing Price Index in Malaysia. There are five independent variables that have been select for this research. The independent variables are consumer price index (MCPI), lending rates (MLR), money supply (MMS), gross domestic product (MGDP) and unemployment rate (MUR). This study use the quarterly data from quarter 3 of 2006 to quarter 1 of 2017 which total number of observation is 43 sample. Multiple linear regression model is applied to study the relationship between explanatory variables and explained variable. Empirical result of Equation 3 shows that MLR, MGDP and MUR significantly affect MHPI. While MCPI and MMS insignificantly affect MHPI. This study shows that the most significant relationship with MHPI is MLR followed by MGDP and MUR.